KAJIAN TINJAUAN LITERATUR DALAM PENELITIAN SOSIAL - Alif, Muhammad; Solihin, Olih (Universitas Swadaya Gunung Jati, 2023)
Literature review plays a crucial role in social research by providing a comprehensive understanding of previous studies, identifying knowledge gaps, and guiding further research. This study aims to conduct a literature review within the field of social research. The research methodology includes determining the scope, identifying data sources from Scopus, Web of Science (WoS), and Google Scholar (GS), data collection through reading and creating a comparison matrix, data analysis, interpretation, and synthesis. Determining the scope of the literature review involves defining the research boundaries and specifying key concepts, themes, and timeframes to be included. The identification of data sources from Scopus, WoS, and GS ensures comprehensive coverage by accessing scholarly articles, journals, conference papers, and other publications in the social sciences. The data collection process involves reading and analyzing selected articles, and extracting key information such as research objectives, methodologies, theoretical frameworks, findings, and knowledge gaps. Data analysis involves examining the information collected from the comparison matrix, identifying significant trends, and establishing connections between different sources. Through thematic analysis, the data is categorized into relevant themes. Data interpretation involves critically analyzing the findings and discussing their implications within the research context. Finally, the data is synthesized by integrating key findings and providing a comprehensive overview of the existing literature on the chosen topic. In conclusion, a literature review in social research provides an in-depth understanding of recent developments, identifies knowledge gaps, and provides a solid theoretical foundation for further research. Keywords: Literature review, social science, methodology, social research